Sistemática y distribución de los oligoquetos marinos (Annelida: Oligochaeta) de la bahía de San Quintín, Baja California, México - Cantú Martínez, Pedro César (1987)
Bahía de San Quintín is a coastal lagoon located 200 km. south from Ensenada, Baja California, México. Systematic samples in 17 stations during July, September and December 1981, and February and April 1982 were done. Seven species were found: Limnodriloides barnardi Cook, 1974, L. monothecus Cook, 1974, Tectidrilus verrucosus (Cook, 1974), T. diversus Erséus, 1982. Thalassodrilides belli (Cook, 1974), Tubificoides postcapillatus (Cook, 1974) and Tubificoides sp. Oligochaetes were more abundant in silty or silty-sand sediments. L. barnardi made up 60% of the collected oligochaetes.